Whole slide imaging in pathology: advantages, limitations, and emerging perspectives - Farahani N; Parwani AV; Pantanowitz L (Dove Medical Press, 2015)
Navid Farahani,1 Anil V Parwani,2 Liron Pantanowitz2 1Department of Pathology and Laboratory Medicine, Cedars-Sinai Medical Center, Los Angeles, CA, USA; 2Department of Pathology, University of Pittsburgh School of Medicine, Pittsburgh, PA, USA Abstract: Significant technologic gains have led to the adoption of innovative digital imaging solutions in pathology. Whole slide imaging (WSI), which refers to scanning of conventional glass slides in order to produce digital slides, is the most recent imaging modality being employed by pathology departments worldwide. WSI continues to gain traction among pathologists for diagnostic, educational, and research purposes. This article provides a technologic review of WSI platforms and covers clinical and nonclinical pathology applications of these imaging systems. Barriers to adoption of WSI include limiting technology, image quality, problems with scanning all materials (eg, cytology slides), cost, digital slide storage, inability to handle high-throughput routine work, regulatory barriers, ergonomics, and pathologists' reluctance. Emerging issues related to clinical validation, standardization, and forthcoming advances in the field are also addressed. Keywords: digital, imaging, microscopy, pathology, validation, whole slide image, telepathology